‘Iddah and Ihd?d for Career Women from Islamic Law Perspective: ‘Iddah dan Ihd?d bagi Wanita Karir Perspektif Hukum Islam - Khoiri, Ahmad; Muala, Asyharul (Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
Islam enforces the iddah period for women who are being divorced by their husbands or their husbands have died. During this waiting period, women are limited in making up or grooming themselves and leaving the house (ihdad). The provision regarding the iddah period becomes problematic when faced with women who have to work to meet the needs of themselves and their families. This paper aims to explain the law for women who continue to carry out their daily lives by working outside the home from an Islamic perspective. The type of research that the author uses in this paper is a literature study. The author concludes that women working during the iddah period do not violate the provisions of the iddah period and continue to carry out the iddah period, even though the woman leaves the house to earn a living and the conditions vary. The prohibition for women during the iddah period is that it is haram to marry another man, it is forbidden to leave the house unless there is an emergency reason and it is obligatory to perform ihdad. Regarding professionalism in work, especially career women in their respective fields, it must be used as a form of carrying out Islamic law and carrying out their nature as a social human being. By considering moral ethics, iddah has protection in modern development, especially for women who are active in their respective fields.